Surface replacement of proximal interphalangeal joint (SR-PIPJ) arthroplasty - A case series - Jordaan, Pieter Willem (Department of Health and Rehabilitation Sciences, 2016)
Surface replacement (SR) proximal interphalangeal joint replacement consists of a cobalt-chrome alloy component articulating with an ultra-high molecular weight polyethylene component. After experiencing a high rate of subsidence and complications with a pyrocarbon implant, our unit has changed to the cemented SR system in the hope of decreasing these complications. The main aim of this study was to determine whether this change in practice has led to a decrease in subsidence and complications. A retrospective chart review was performed including 43 joints in 28 patients. Subsidence was noted in 26% of the joints and complications in 31% of the joints. Even though subsidence remains a problem, the change in implant has led to a decrease in subsidence and other complications.